Knowledge, Attitude, and Testing of Human Immunodeficiency Virus Infection among 15- to 49-year-old Women in Sudan: An Analysis of the United Nations Children's Fund-Multiple Indicator Cluster Survey - Sagad Omer Obeid Mohamed; Hajir Mohamed Attaalmanan Ali; Esraa Abdeldaiem Mohamedien Ali; Samia Ali Mohammed Mustafa; Sana Hassan Mohamad Hassan; Thweaba Hassan Salih Omer; Fatima Ammar Hamed Suliman (Dr. Sulaiman Al Habib Medical Journal)
Human Immunodeficiency Virus (HIV) infection is a major public health challenge worldwide. Evidence suggests that health- related behaviours are affected by the knowledge, attitude, and practice of individuals. The aim of this study was to assess the knowledge, attitude, and testing of HIV infection, and their associated factors among women of the reproductive age group in Sudan. We used the latest available data (2014) of the Sudan-Multiple Indicator Cluster Survey (MICS) obtained from the United Nations Children’s Fund (UNICEF). Assessment of the knowledge, attitude, and testing of HIV infection, and their associated factors was performed using descriptive statistics, Chi-square test, and logistic regression analysis. A total of 12,703 women were included in this analysis. Only 38.1% of the respondents had an adequate level of knowledge about HIV infection, and 22.3% of them had a favourable attitude and tolerance toward dealing with HIV-infected persons. Both adequate knowledge and favourable attitude toward HIV patients were significantly associated with urban residence, higher level of education, and wealth index groups. The proportion of HIV testing among the respondents was only 4.30%, and the factors associated with HIV testing were urban residence [Odds Ratio (OR) = 2.482], highest levels of education (OR = 3.066), and highest wealth index groups (OR = 1.443). The study showed that a significant proportion of the participants lack requisite knowledge about HIV infection and a low level of HIV testing coverage. Further efforts are required to increase awareness of HIV and to disperse myths and misguided judgments regarding HIV infection.